In (the) Place of the Self: A Critical Study of Jean-Luc Marion's "Au Lieu De Soi. L'approche De Saint Augustin" - Schrijvers, Joeri (Modern theology, 2009)
This review article discusses Jean-Luc Marion's latest book Au lieu de soi. L'approche de Saint-Augustin, in which Marion lets the theology and phenomenology of givenness interact with Augustine's œuvre. The article provides an extensive summary of Marion's book and offers a critical analysis by linking Au lieu de soi to Marion's earlier work. Apart from this, this review hopes to open some parallels with the work of Emmanuel Levinas and Jean-Yves Lacoste if only to show how easily a certain strand of Augustinianism blends with contemporary thought.